Inter-Organ Relationships of the Thymus and Spleen in the Dynamics of Temperature Exposure (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The central (thymus, bone marrow) and peripheral (spleen, mesenteric lymph nodes) organs of the immune system in the dynamics of temperature exposure have been studied by complex morphological methods. Separate periods of immunomorphological adaptive rearrangements of the organs of the immune system in response to antigenic effects were established: early changes (3-24 hours of the experiment), pronounced immunomorphological rearrangements (from 3 to 14 days of the experiment) and reconvalescence (from 14 to 21 days of the experiment). Each of these periods is characterized by the dynamics of morphological and functional changes that ensure immune homeostasis in response to temperature exposure.